KEPUASAN TAMU TERHADAP KUALITAS PELAYANAN ROOM BOY HOTEL GRAND JATRA PEKANBARU - Ajis, Ridho Abdul; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Hotel include business presses on sales of service. One of the activities undertaken by the company to achieve sales goals is to implement good and efficient service to consumers. Without this kind of service efforts to increase sales volume is very difficult because of the many and tight competition that occurs today. This study aims to find out how the quality of service Grand Jatra Pekanbaru Hotel. This research uses quantitative descriptive method to examine the problem in the lift by analyzing the guest response about the service room boy Grand Jatra Pekanbaru Hotel. The questionnaires were distributed as many as 100 people. While data colection techniques in this study using observation, questionnaires, and documentation. The results showed that respondents assessed the quality of service room boy Grand Jatra Pekanbaru Hotel is good. It is proven through the results of the average total gain of each of the overall variables reliability (33,5%), responsiveness (51%), assurance (45%), emphaty (35%), tangible(43%). The conclusion obtained from guest satisfaction with the quality of room boy service is quite satisfied. Thus the quality of room boy services provided by the Grand Jatra Pekanbaru Hotel can be maintained or improved. Keywords : service quality, roomboy, hotel